Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1093/ajcp/81.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Intestinal Perforation Caused by Congenital Defects of the Intestinal Musculature

Abstract: Spontaneous perforation of the small intestine in the newborn is rare. In most cases the etiology is unknown. Three cases of perforation in preterm newborn infants are described. The clinical diagnosis was necrotizing enterocolitis (NEC), and an urgent laparotomy was performed. The histologic examination was compatible with the diagnosis of a congenital defect of the intestinal musculature. All three infants survived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 8 publications
2
30
0
Order By: Relevance
“…5 As evidence for this hypothesis, previous authors had noted the same pathologic findings subsequently found in SIP of the ELBW infant. 6,7 Our ability to capture this subset of patients, who are significantly more likely to be male and seem to have perforations in transit out of the womb, reinvigorates the postulate that SIP can be acquired congenitally.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…5 As evidence for this hypothesis, previous authors had noted the same pathologic findings subsequently found in SIP of the ELBW infant. 6,7 Our ability to capture this subset of patients, who are significantly more likely to be male and seem to have perforations in transit out of the womb, reinvigorates the postulate that SIP can be acquired congenitally.…”
Section: Discussionmentioning
confidence: 97%
“…Before the improved survival of ELBW infants, SIP was thought to be a congenitally acquired disease that affects term and near term infants (old SIP). [5][6][7] These case reports described segmental absence of the muscularis in the distal intestine either as an isolated or multifocal process, with some infants having a single occurrence and others having recurrent presentations. The difference in presumed etiology between the old SIP and the new SIP has never been resolved but reports of the old SIP have declined in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the pathogenesis of the muscular defect is divided into two types, congenital and acquired [3]. In the congenital type [2,4], the intact mucosa with long villi, good epithelialization, and the edematous, congested submucosal layer make it appear unlikely that the cause of the muscle defect is transmural ischemia, suggesting that the defect may be congenital. Although there were short mucosal villi and dilated vessels in our cases, short villi can regenerate after ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…There are no prodromal GI symptoms or radiographic sings of NEC such as persistent dilated loops or pneumatosis intestinalis, or portal-vein gas. The etiologic factors that have been proposed [1] include umbilical catheters, indomethacin therapy, cytomegalovirus infection, coagulase-negative staphylococcal infection [5], and congenital defects of the intestinal musculature [4].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of being congenital [16] or acquired [17], defects in the intestinal musculature have been reported as a cause of FIP. From these histological findings and the fact that FIP occurs exclusively in very-low-birth-weight neonates, we speculate that immature or uncoordinated bowel movement causes a localized increase in intraluminal pressure and leads to focal perforation or bulging at the sites of defects of muscular layer.…”
Section: Histological Findings Around the Perforationmentioning
confidence: 99%